(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This study aims to determine the influence of Islamic Corporate Governance and Islamic Social Reporting on company value through financial performance. This study uses a quantitative method with an explanatory approach. The data used in this study is secondary data with the data collection method using a purposive sampling method with 20 samples of consumer goods industry companies registered at ISSI during the period 2018 to 2021. The independent variable in this study is Islamic Corporate Governance and Islamic Social reporting. While the dependent variable is the value of the company. And financial performance as a moderating variable. Hypothesis testing is done by using software Eviews. 12. The results of the research show that Islamic Corporate Governance has a significant effect on firm value. Meanwhile Islamic Social Reporting has no effect on firm value. And financial performance cannot moderate the influence of Islamic Corporate Governance and Islamic Social reporting to company value.